PENERAPAN METODE MAKE AND MATCH DAPAT MENINGKATKAN KEAKTIFAN BELAJAR SOSIOLOGI PADA SISWA KELAS X3 SMA NEGERI 1 GUNUNG TULEH KABUPATEN PASAMAN BARAT - renywaty renywaty (STKIP Pesisir Selatan, 2017)
AbstractSociology is one of the subjects that could make people understand themselves and their surroundings, that foster the harmony of life and have a good mental to carry out positive activities.The research objective of this class action is to enhance the activity of studying Sociology in class X SMAN 1 Gunung Tuleh West Pasaman using the Make and Match. This classroom action research conducted in SMA Negeri 1 Mount Tuleh West Pasaman in class X in Ganji semester of academic year 2014/2015. Number of students 30 people.Discussion involving undertaken by students to run well and smoothly, as shown in observations of students in the group collaborative activities